2011
DOI: 10.1177/0363546511399383
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Spontaneous Hyaline Cartilage Regeneration Using a Double-Network Gel

Abstract: This study has prompted us to develop a potential innovative strategy to repair cartilage lesions in the field of joint surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…This discovery has proposed a novel strategy to repair an osteochondral defect in the field of joint surgery using the artificially synthesized hydrogel without any cultured cells or mammalian-derived scaffolds. We, therefore, have confirmed the efficacy of this therapeutic strategy with the 5-mm thick DN gel plug not only in the patellofemoral joint but also in the femorotibial joint [16,17]. However, this therapeutic strategy with use of the 5-mm thick DN gel plug has some drawbacks from the clinical viewpoint: Namely, to implant the 5-mm thick DN gel plug, we have to make a 7- to 8-mm deep bone defect by surgically scraping the bottom of the defect.…”
Section: Introductionmentioning
confidence: 78%
“…This discovery has proposed a novel strategy to repair an osteochondral defect in the field of joint surgery using the artificially synthesized hydrogel without any cultured cells or mammalian-derived scaffolds. We, therefore, have confirmed the efficacy of this therapeutic strategy with the 5-mm thick DN gel plug not only in the patellofemoral joint but also in the femorotibial joint [16,17]. However, this therapeutic strategy with use of the 5-mm thick DN gel plug has some drawbacks from the clinical viewpoint: Namely, to implant the 5-mm thick DN gel plug, we have to make a 7- to 8-mm deep bone defect by surgically scraping the bottom of the defect.…”
Section: Introductionmentioning
confidence: 78%
“…Based on the previous studies reporting cartilage regeneration using a DN gel, the depth of the defect remained after the DN gel implantation is a critical factor on the cartilage regeneration induced by the DN gel: An approximately 2-mm deep vacant space above the DN gel is the most effective for cartilage regeneration in a mature rabbit femoral trochlea osteochondral defect model [17, 1921], this suggests that the appropriate size of space is very important for regeneration of high quality cartilage tissue. The present study used a 2-mm depth model and showed cartilage regeneration in the vacant space independent on the defect size at 4 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In the right knee of each animal, a cylindrical DN gel plug was implanted at the bottom of each defect so that a 2-mm deep defect remained above the DN gel after surgery. The depth of 2 mm was chosen because this depth was found to be the most effective to induce the cartilage regeneration in our previous study with rabbits [17, 21]. In the left knee, a defect was left vacant without any implantation to obtain control data.…”
Section: Methodsmentioning
confidence: 99%
“…Previous in vivo studies showed that the mechanical properties of the PAMPS/PDMAAm DN gel implanted in the subcutaneous tissue did not deteriorate at 6 weeks after implantation [10] and that although a pellet implantation test into the para-vertebral muscle induced a mild cell infiltration at 1 week, the degree of the inflammation significantly decreased to the same degree as that of the negative control at 4 and 6 weeks [21]. Furthermore, the shape or the position of the PAMPS/PDMAAm DN gel implanted in the bone defect was not much changed at 12 weeks after surgery compared to that at 4 weeks [2]. We also cultured ATDC5 cells on the PAMPS/PDMAAm DN gel [1] as well as the single-network PAMPS and PDMAAm gels [4,5].…”
Section: Discussionmentioning
confidence: 99%